2005
DOI: 10.3758/bf03193329
|View full text |Cite
|
Sign up to set email alerts
|

Audio-visual simultaneity judgments

Abstract: The relative spatiotemporal correspondence between sensory events affects multisensory integration across a variety of species; integration is maximal when stimuli in different sensory modalities are presented from approximately the same position at about the same time. In the present study, we investigated the influence of spatial and temporal factors on audio-visual simultaneity perception in humans. Participants made unspeeded simultaneous versus successive discrimination responses to pairs of auditory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
205
4
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 246 publications
(245 citation statements)
references
References 62 publications
33
205
4
3
Order By: Relevance
“…In general, the psychophysical results of the present study are in line with the findings of previous work (Grondin & Rousseau, 1991;Zampini, Brown, et al, 2005;Zampini, Guest, et al, 2005). When testing for ordering effects of the modalities defining an interval, we find that intervals with an auditory onset are perceived to be longer than intervals with an auditory offset (i.e., audio-visual intervals are perceived longer than visual-audio and audio-tactile intervals longer than tactile-audio).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In general, the psychophysical results of the present study are in line with the findings of previous work (Grondin & Rousseau, 1991;Zampini, Brown, et al, 2005;Zampini, Guest, et al, 2005). When testing for ordering effects of the modalities defining an interval, we find that intervals with an auditory onset are perceived to be longer than intervals with an auditory offset (i.e., audio-visual intervals are perceived longer than visual-audio and audio-tactile intervals longer than tactile-audio).…”
Section: Discussionsupporting
confidence: 82%
“…Across all modality pairs, we find a trend to overestimate short SOAs and to underestimate long SOAs which is consistent with the range effect reported by von Vierordt (1868). Furthermore, consistent with previous studies (Grondin & Rousseau, 1991;Zampini, Brown, et al, 2005;Zampini, Guest, et al, 2005), we find that intervals with an auditory onset are perceived to be longer than intervals with an auditory offset. For visualtactile intervals there is no difference in perceived duration depending on whether the visual or the tactile signal marks the onset of the interval.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, when the asynchronously presented auditory and visual stimuli are presented from different locations (i.e., when the auditory stimuli are presented via headphones while the visual stimuli are still presented in front of the participant), this results in changes in the perceptual latency of the auditory stimuli instead. Zampini et al (2005) also found that, when required to judge the simultaneity of auditory and visual stimuli, participants were more likely to report them as having been presented simultaneously when the stimuli were presented from the same spatial position than when they originated from different spatial positions.…”
Section: Resultsmentioning
confidence: 95%
“…Zampini, Guest, Shore, & Spence, 2005). The order of presentation of the blocks (spatially uninformative, spatially informative) was counterbalanced, and the blocks were presented in alternating order.…”
Section: Methodsmentioning
confidence: 99%